Fault tree analysis of cargo leakage from manifold connection in fuzzy environment: A novel case of anhydrous ammonia. (15th October 2021) - Kuzu, Ali Cem; Senol, Yunus Emre
Abstract: Ammonia cargo requires special expertise in terms of handling, storage and transportation aspects as it is unquestionably one of the toughest goods carried by tankers due to its intrinsically dangerous properties. Any malfunction experienced during the cargo operation may result in disasters. Cargo manifold leakage is one of the most critical hazards that may arise during cargo operations. According to the characteristics of the ammonia, manifold leakages contain risks that may result in explosion, fire, pollution and poisoning. In this study, all probable root causes and risk of cargo manifold leakage event of a gas tanker carrying ammonia is introduced by employing Fault Tree Analysis (FTA) in fuzzy environment, which is a systematic method to access reliability of complex systems both quantitatively and qualitatively by using exact occurrence probability values of all probable root causes. As a result, occurrence probability of ammonia leakage from cargo manifold is calculated as 0.00539 which is found realistic by consulted field experts. This study aims to introduce an appropriate management tool to identify root causes and mitigate the cargo manifold leakage risk by reducing the occurrence probabilities of the root causes. Highlights: Failure probability of ammonia leakage from manifold Top Event is obtained as 0.00539. Basic event of "Draft change" is found in each the most prior 6 minimal cut sets. Human element directly or indirectly is found as main and the most effective root cause for this study. MCSs of Incorrect Screw and Incompatible Arm/Hose, and Missing Bolt/Nut and Incompatible Arm/Hose have the lowest priority.